Integrasi Pendidikan Multikultural dalam Buku Teks Ilmu Pengetahuan Alam untuk Siswa Kelas V Sekolah Dasar di Lombok Timur - Lia Rismawati; Aswasulasikin Aswasulasikin; Nuraini Nuraini (STKIP Singkawang, 2022)
Penelitian ini bertujuan mendeskripsikan pengintegrasian pendidikan multikultural yang terdapat dalam buku teks IPA Sekolah Dasar (SD) kelas V. Pendekatan penelitian menggunakan penelitian kualitatif. Sumber data berupa buku teks IPA yang digunakan di SD wilayah Kecamatan Sikur. Data dikumpulkan dengan observasi dan analisis dokumen serta dianalisis menggunakan analisis interaktif dengan tahapan reduksi data, penyajian data, dan penarikan simpulan/verifikasi. Nilai-nilai pendidikan multikultural dari empat Buku Teks IPA untuk SD yang digunakan di Kabupaten Lombok Timur telah terintegrasi akan tapi pengintegrasiannya masih monoton pada budaya mayoritas. Terdapat enam subdimensi dari sembilan subdimensi yang ada. Subdimensi yang dimaksud, yakni: subdimensi budaya dalam dimensi integrasi materi; subdimensi pemahaman dalam dimensi merekonstruksi pengetahuan; subdimensi individu dalam dan kelompok dalam dimensi penyesuaian metode pembelajaran; subdimensi agama dalam dimensi pengurangan prasangka; subdimensi budaya sekolah dalam dimensi penguatan budaya sekolah dan struktur sosial. Sementara subdimensi individu, agama, suku/ras/etnis, demokrasi, dan struktur sosial tidak terintegrasi dalam buku ini. Sementara pada buku empat ditemukan subdimensi budaya, pemahaman, kelompok, agama, dan budaya sekolah. Pola pengintegrasian pendidikan multikultural dalam keempat buku tersebut terdiri dari integrasi dalam bentuk wacana, komik, cerita, dan latihan dalam tiap tema pembelajaran.Kata Kunci: Pendidikan Multikultural; Buku Teks; IPA Integration of Multicultural Education in Natural Science Textbooks for Grade V Elementary School Students in East LombokABSTRACTThis study aims to describe the integration of multicultural education in the fifth-grade elementary school science textbooks. The research approach used qualitative research. The data source was in the form of science textbooks used in elementary schools in the Sikur District. Data were collected by observation and document analysis and analyzed using interactive analysis with the stages of data reduction, data presentation, and concluding/verification. The values of multicultural education from the four science textbooks for elementary schools used in East Lombok Regency had been integrated but the integration is still monotonous in the majority culture. There were six sub-dimensions of the nine existing sub-dimensions. The sub-dimensions in question were the cultural sub-dimension in the material integration dimension; sub-dimension of understanding in the dimension of reconstructing knowledge; individual and group sub-dimensions in the dimension of learning method adjustment; sub-dimension of religion in the dimension of reducing prejudice; sub-dimension of school culture in the dimensions of strengthening school culture and social structure. Meanwhile, individual sub-dimensions, religion, ethnicity/race/ethnicity, democracy, and social structure are not integrated into this book. Meanwhile, in book four, the sub-dimensions of culture, understanding, group, religion, and school culture are found. The pattern of integrating multicultural education in the four books consists of integration in the form of discourse, comics, stories, and exercises in each learning theme.